6
$\begingroup$

So I have this series:

$$\displaystyle\sum_{n=1}^{\infty}\frac{3n^2+15n+9}{n^4+6n^3+9n^2}$$

I noticed:

$$\displaystyle\sum_{n=1}^{\infty}\frac{1}{n^2}(\frac{3n^2+15n+9}{n^2+6n+9})$$

So can I say that it's convergent already or should I use a critera on the second fraction in the sum?

Also for sum I could use partial fractions or am I mistaken?

Any help would be appreciated.

$\endgroup$
  • $\begingroup$ Note that $n^2+6n+9=(n+3)^2$. Also, Wolfram Mathematica gives $\frac{115}{36}$ for the limit of your sum. $\endgroup$ – vrugtehagel Feb 15 '16 at 14:03
  • $\begingroup$ also i can take 3 out of the numerator $\endgroup$ – MathIsTheWayOfLife Feb 15 '16 at 14:05
  • $\begingroup$ Unless you are looking to find the exact sum, you should be able to do a direct comparison test to something like $\sum\frac{1}{n^2}$. If finding how to correctly use the inequalities in this case is difficult, then a ratio test might be easier. $\endgroup$ – JMoravitz Feb 15 '16 at 14:08
  • $\begingroup$ thank you , i appreciate it $\endgroup$ – MathIsTheWayOfLife Feb 15 '16 at 14:11
  • $\begingroup$ And... $$\sum_{n=1}^{\infty}\frac{1}{n^2}\cdot\frac{3n^2+15n+9}{n^2+6n+9} = \sum_{n=1}^{\infty}\frac{3}{n^2}\cdot\frac{n^2+5n+3}{n^2+6n+9} = 3\sum_{n=1}^{\infty}\frac{1}{n^2}\left(1 - \frac{n+6}{n^2+6n+9}\right)$$ ...which may help you, or may be not. $\endgroup$ – CiaPan Feb 15 '16 at 14:59
10
$\begingroup$

You can conclude that the series converges by the comparison test. We can also calculate the sum. Note that $$\frac{3n^{2}+15n+9}{n^{4}+6n^{3}+9n^{2}}=\frac{1}{n^{2}}+\frac{1}{n}-\frac{1}{n+3}-\frac{1}{\left(n+3\right)^{2}} $$ hence $$\sum_{n\geq1}\frac{3n^{2}+15n+9}{n^{4}+6n^{3}+9n^{2}}=\sum_{n\geq1}\left(\frac{1}{n^{2}}+\frac{1}{n}-\frac{1}{n+3}-\frac{1}{\left(n+3\right)^{2}}\right)$$ $$=2+\frac{1}{2}+\frac{1}{4}+\frac{1}{3}+\frac{1}{9} =\frac{115}{36} $$ because the series telescopes.

$\endgroup$
5
$\begingroup$

Consider

\begin{align} a_n=\frac{3n^2+15n+9}{n^4+6n^3+9n^2} &\le \frac{3n^2+15n^2+9n^2}{n^2(n+3)^2} \\ &= \frac{27}{(n+3)^2}\\ &\le \frac{27}{n^2} = b_n \end{align}

It is well know that

$$\sum_{n=1}^\infty \frac{1}{n^2}$$

converges. Since $0\le a_n\le b_n$ and $\sum b_n$ converges, we may conclude that $\sum a_n$ converges.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.